SARS-CoV-2 Neutralizing Antibody LY-CoV555 in Outpatients with Covid-19 - Chen, Peter; Nirula, Ajay; Heller, Barry; Gottlieb, Robert L; Boscia, Joseph; Morris, Jason; Huhn, Gregory; Cardona, Jose; Mocherla, Bharat; Stosor, Valentina; Shawa, Imad; Adams, Andrew C; et al. (The New England journal of medicine, 2021)
In a phase 2 trial, outpatients with Covid-19 who received a single infusion of a 2800-mg dose of the neutralizing antibody LY-CoV555 had a greater reduction from baseline in viral load than those who received placebo. Hospitalization was less frequent among antibody-treated patients (1.6% vs. 6.3%).